2017
DOI: 10.14411/fp.2017.026
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in the distribution and directional asymmetry of fleas living on the northern white-breasted hedgehog Erinaceus roumanicus

Abstract: Fleas infecting northern white-breasted hedgehogs, Erinaceus roumanicus (Barrett-Hamilton), collected from 2009-2011 in Budapest (Hungary) were studied. A total of 305 white-breasted hedgehogs were captured and 1,251 fleas were collected. The flea community comprised two species, the hedgehog flea Archaeopsylla erinacei (Bouche, 1835) and the dog flea Ctenocephalides canis (Curtis, 1826), although the latter was only found on three hedgehogs. Fleas were found on half of the host specimens (51%; n = 156) where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…In addition to hedgehog-specific flea species, such as Archaeopsylla erinacei and Hystrichopsylla talpae, other flea species that typically parasitise other animals, such as dogs, cats, and birds, can also be found in these mammals [19,46,47]. Infected hedgehogs may show signs of weakness, itching, and, in severe cases, anaemia [46].…”
Section: Fleasmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to hedgehog-specific flea species, such as Archaeopsylla erinacei and Hystrichopsylla talpae, other flea species that typically parasitise other animals, such as dogs, cats, and birds, can also be found in these mammals [19,46,47]. Infected hedgehogs may show signs of weakness, itching, and, in severe cases, anaemia [46].…”
Section: Fleasmentioning
confidence: 99%
“…Infected hedgehogs may show signs of weakness, itching, and, in severe cases, anaemia [46]. Despite their direct impact on hedgehogs, A. erinacei is particularly relevant due to the potential transmission of pathogenic agents [47][48][49][50]. Hornok et al (2014) have identified Rickettsia helvetica and Bartonella henselae in fleas of the species A. erinacei parasitising hedgehogs [50].…”
Section: Fleasmentioning
confidence: 99%
“…On the other hand, hedgehogs inhabit rural, urban, and suburban environments, and they are frequently parasitized by blood-sucking arthropods, such as hard ticks and fleas, including the hedgehog flea, Archaeopsylla erinacei Bouché, 1835, and other flea species such as C. felis , C. canis , and Nosopsyllus fasciatus Bosc, 1800 [ 32 , 33 , 34 , 35 ]. Since they usually cohabit with pets and humans, they can potentially act as reservoirs of pathogen microorganisms responsible for zoonoses [ 12 ].…”
Section: Introductionmentioning
confidence: 99%